The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2001
DOI: 10.1007/s002470100001
|View full text |Cite
|
Sign up to set email alerts
|

Spiral CT scanning technique in the detection of aspiration of LEGO foreign bodies

Abstract: Rapid, low-dose spiral CT may be used to visualize LEGO FBs in the airway or esophagus. Peanuts were not well visualized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 0 publications
0
29
0
1
Order By: Relevance
“…Even nonradio-opaque material, such as plastic LEGO pieces, have been detected in cadavers [15]. Compared to the diagnosis based on symptoms and the chest X-ray, the 3D-CTVB can increase the sensitivity (100%) and speciWcity (81-100%) of the diagnosis [8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Even nonradio-opaque material, such as plastic LEGO pieces, have been detected in cadavers [15]. Compared to the diagnosis based on symptoms and the chest X-ray, the 3D-CTVB can increase the sensitivity (100%) and speciWcity (81-100%) of the diagnosis [8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Early on, it was shown that radiolucent foreign bodies could be found by CT scan in children [15]. A study in a cadaver model using low-dose spiral CT scan reported a combined sensitivity of 89% and combined specificity of 89%, although peanuts, in particular, were not well visualized [8]. Recently, the resolution of the threedimensional chest CT scan has increased, and a threedimensional surface-rendered image can now also clearly delineate airway defects formed by FBA.…”
Section: Discussionmentioning
confidence: 95%
“…Wheezing in the absence of known pulmonary disease, especially if unilateral, should be considered to be due to FBA until proven otherwise [8].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, coins are the most common (Reilly and Walter 1992), followed by plastic toy pieces and sharp objects such as pencils and pull-tabs from aluminum cans (Rogers and Igini 1975;Burrington 1976;Blazer et al 1980;Strickland et al 1987;Applegate et al 2001). Inert foreign bodies have little effect on the bronchial mucosa and, unless they cause an obstruction by virtue of their size, can remain undiagnosed for long periods of time (Adegboye et al 2003).…”
Section: Etiology/types Of Foreign Bodiesmentioning
confidence: 97%
“…CT is also an efficient tool for the demonstration of small plastic toy particles such as LEGO pieces (Applegate et al 2001) or rubber products. The presence and location of an intraluminal lesion can easily be detected and multiple intrabronchial findings can at times be identified (Figs.…”
mentioning
confidence: 99%